2013
DOI: 10.1074/jbc.m113.459602
|View full text |Cite
|
Sign up to set email alerts
|

Microsomal Triglyceride Transfer Protein Inhibition Induces Endoplasmic Reticulum Stress and Increases Gene Transcription via Ire1α/cJun to Enhance Plasma ALT/AST

Abstract: Background: Microsomal triglyceride transfer protein (MTP) inhibition augments plasma transaminases, however, mechanisms are unknown. Results: MTP inhibition increased endoplasmic reticulum (ER) stress and induced GPT/GOT1 transcription through the Ire1␣/cJun pathway. Conclusion: Transcriptional up-regulation and increased synthesis contribute to augmentations in plasma ALT/AST. Significance: Increased transcription of the transaminase genes may reflect a mechanism for hepatocyte survival after ER stress.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
45
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 51 publications
(52 citation statements)
references
References 37 publications
3
45
0
Order By: Relevance
“…However, statins reduce plasma lipids by only 30-40%, and high doses can cause muscle weakness [37,38]. Additionally, MTP inhibitors increase plasma transaminases and cause hepatic steatosis [39][40][41][42][43][44][45][46]. Hence, there is a need for agents that can lower plasma lipids and avoid sideeffects associated with these therapies.…”
Section: Microrna-30c and Lipid Metabolismmentioning
confidence: 96%
“…However, statins reduce plasma lipids by only 30-40%, and high doses can cause muscle weakness [37,38]. Additionally, MTP inhibitors increase plasma transaminases and cause hepatic steatosis [39][40][41][42][43][44][45][46]. Hence, there is a need for agents that can lower plasma lipids and avoid sideeffects associated with these therapies.…”
Section: Microrna-30c and Lipid Metabolismmentioning
confidence: 96%
“…8). The increase in hepatic free cholesterol in the livers of male Gpat3 Ϫ/Ϫ mice was accompanied by increased ALT/AST serum levels; interestingly, increases in hepatic cholesterol and CE, but not hepatic triglycerides, have been previously linked to increased ALT/AST levels (13). Using a mass spectrometry-based approach, we also examined the composition of specific lipid species in liver and epididymal and subcutaneous fat depots but were unable to discern any significant alterations in the composition of TAG, DAG, SM, and PC (data not shown).…”
Section: Gpat3mentioning
confidence: 98%
“…We previously reported that hepatic MTP deficiency increases free cholesterol in the livers of Western diet-fed mice or mice with hepatic LDL receptor deficiency, and this effect leads to endoplasmic reticulum stress and release of alanine and aspartate aminotransferases (36,43). Surprisingly, free cholesterol did not accumulate significantly in the intestine of I-Mttp Ϫ/Ϫ mice.…”
Section: Roles Of Intestinal Mtp and Abca1 In Tissue Lipidmentioning
confidence: 99%
“…Altered Free Fatty Acid Metabolism in MTP-and ABCA1-deficient Enterocytes-Triglyceride accumulation is universally observed in hepatic (6,36) and in intestine-specific deficiencies of MTP (7). However, although FFA accumulation has not been observed in the liver-specific MTP knock-out mice (6, 36), intestine-specific MTP ablation has been reported to increase cellular free fatty acids (7).…”
Section: Mtp and Abca1 Gene Ablations Reduce Cholesterol Secretion Bymentioning
confidence: 99%